KEBIJAKAN RUANG TERBUKA HIJAU PARTISIPATIF (STUDI RTH SASANDO KOTA KUPANG) - , John Peter Palla, SSTP ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Public problems are also governmentâs problem. Low economic and educational level of society could motivate the community to penetrate into government properties. This was compounded by the inconsistency of government agency on their policy implementation. The problems and needs of stakeholders should be accommodated in the policy, therefore, writer make a policy analysis on the formulation of participatory green open space policy in Kupang city. This research is using agenda setting, formulation of participatory policy, and sustainable development concepts. Research method is qualitative. Informants in this research were determined according to the research goal criteria. Data collection was done through observation, depth interview, and documentation. From field data and analysis, the results are: to assign Sasando Green Open Space as a fixed green open space, gives a private green open space status to the occupant who have legal land status, together with private company build a city park around the green open space in which business space is provided for community around it, and build supporting infrastructure for green open space.